2019
DOI: 10.1021/acsbiomaterials.9b01257
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Ag Nanoparticles from Neem Extract: Their Structural Evaluation and Antimicrobial Effects against Pseudomonas nitroreducens and Aspergillus unguis (NII 08123)

Abstract: Silver nanocrystals have been successfully fabricated by the bioreduction route using the ethanolic extract of Azadirachta indica (neem) leaves as the reducing and capping agent without solvent interference. The silver nanocrystals were grown in a single-step method, without the influence of external energy or surfactants, and at room temperature. The nanoparticles were prepared from different ratios of silver ions to reducing agent molecules and were characterized by UV–vis spectroscopy and transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 58 publications
4
33
0
Order By: Relevance
“…It confirms that the increasing incubation period affects the morphological attributes of AgNP. A narrow and symmetrical peak showed that the nanoparticles are monodisperse and spherical [13]. Our results are in favor of some previously published reports [7,27,28].…”
Section: Phytosynthesis Of Agnps (Spectrophotometric Studies)supporting
confidence: 55%
See 2 more Smart Citations
“…It confirms that the increasing incubation period affects the morphological attributes of AgNP. A narrow and symmetrical peak showed that the nanoparticles are monodisperse and spherical [13]. Our results are in favor of some previously published reports [7,27,28].…”
Section: Phytosynthesis Of Agnps (Spectrophotometric Studies)supporting
confidence: 55%
“…Aqueous extract of the branches was prepared by taking a 1 to 10 ratio of plant material and distilled water respectively and heated on a hot plate at 45°C-65°C for 10-20 min. After the boiling, the aqueous extract was filtered under vacuum by using celite and used immediately as fresh for the reduction of silver salt into AgNPs [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher the concentration of the AgNPs higher the SPR band and vice versa. 12 It was confirmed that the temperature is not only the factor to design the nanoparticles but the concentration of the metallic salt also contributes toward the synthesis along with the incubation period. It was also observed that the SPR band was shifted gradually toward the longer wavelength with an increase in the incubation period (Redshift).…”
Section: Synergistic Effects Of Different Physicochemical Reaction Comentioning
confidence: 94%
“…10,11 Cancer is reported as a leading cause of death with around more than 10 million cases every year and is caused by clonally selected mutations in key tumorsuppressor genes and oncogenes. 12 Conventional treatment of cancer involves the surgical removal of cancer sites, chemotherapeutic and radioactive killing of the cancer cells but these treatments often lead to the deterioration of the patient's body and development of resistance in cancer cells against treatment that negatively affect the treatment success rate. [13][14][15] Colorectal cancer is the third most common cancer and makes 10% of all reported cases worldwide.…”
Section: Introductionmentioning
confidence: 99%